Determinants of Factors Associated With Low Use of IUD Cotraceptions in the Work Area of Puskesmas Sidomulyo Pekanbaru - Kiki Megasari; Yulrina Ardhiyanti (Institute of Computer Science (IOCS), 2021)
Intra Uterine Device (IUD) is one of the MKJP which has many advantages compared to other contraceptive methods. Among the advantages is its high effectiveness so that it can increase the comfort of husband and wife relationships and can be effective immediately after installation with an effective duration of 5 to 10 years, but in fact, fertile age couples (PUS) prefer non-MKJP contraceptives, one of which is injectable contraceptives and pills. . Based on data from the Riau Provincial Health Office, in 2015 the ratio of injectable and IUD KB acceptors in Riau Province was 88.8% injectable KB acceptors and 1% IUD KB acceptors. In 2017, the number of injectable KB acceptors increased to 54.66% and 3.67% of IUD KB acceptors. The lowest use of IUDs in the entire city of Pekanbaru is Sidomulyo Health Center with a percentage of 1.8%. “Active family planning participants are 9,185 with a total of 12,220 PUS. What is assumed to be one of the causes is the lack of knowledge of EFA about IUDs so that factors related to the use of IUDs in EFA are sought. This type of research is quantitative analytic with a cross sectional design, the population in this study is EFA with a sample of 162 respondents. Sampling was done by Systematic Random Sampling. The measuring instrument used is a questionnaire. The results of the statistical test showed that there was a relationship between knowledge (Pvalue = 0,003) (POR= 3,261) (CI) 95% = 1,521-6,992, attitude (Pvalue = 0,001) (POR= 3.60(CI) 95% 1.685-7.691), husband's support (Pvalue = 0,002) (POR= 3,497) (CI) 95%=1,628-7.510, the role of health workers (Pvalue = 0,004) (POR= 3,112) (CI) 95%= 1,472-6,579. This research can be used as a reference as additional material in learning and add useful discourse, for further research in order to be able to develop new knowledge and insights in the field of research. It is hoped that health workers can further improve the provision of information regarding the selection and use of contraceptives as well as the perceived benefits and side effects of EFA by delivering information according to their level of education and understanding.